2010
DOI: 10.1192/pb.bp.108.023077
|View full text |Cite
|
Sign up to set email alerts
|

Controlled comparison of two crisis resolution and home treatment teams

Abstract: Aims and methodTo compare an existing crisis resolution service with a new crisis resolution team (CRT) in Wales. The impact of the new team was measured by changes in bed days and admissions. A random sample of patients from each service was assessed for service satisfaction, social functioning and quality of life after first presentation.ResultsThe total number of bed days was reduced following the introduction of the new CRT (27.3%). The frequency and duration of compulsory admissions increased by 31% in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
3
29
1
2
Order By: Relevance
“…Our findings reflect an overall reduction in admissions and are in stark contrast to the finding by Tyrer et al that introduction of CRHT reduced informal admissions but was accompanied by increased numbers of compulsory admission. 11 Our results replicated the finding of Johnson et al that there was a reduction in compulsory admissions with the introduction of CRHT but that this was not significant. 8 Tyrer et al hypothesised that the work of CRHT teams maintains patients in the community, preventing informal admissions, but results in some patients' condition deteriorating to such a point that compulsory admission is eventually necessary.…”
Section: Contextsupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings reflect an overall reduction in admissions and are in stark contrast to the finding by Tyrer et al that introduction of CRHT reduced informal admissions but was accompanied by increased numbers of compulsory admission. 11 Our results replicated the finding of Johnson et al that there was a reduction in compulsory admissions with the introduction of CRHT but that this was not significant. 8 Tyrer et al hypothesised that the work of CRHT teams maintains patients in the community, preventing informal admissions, but results in some patients' condition deteriorating to such a point that compulsory admission is eventually necessary.…”
Section: Contextsupporting
confidence: 82%
“…11 In contrast to this, our CRHT teams covered a wide and socially diverse geographic area, which may account for some of the differences in findings and may indicate that our results are more generalisable to services in other, larger catchment areas.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…This phenomenon has been observed previously, forwith the introduction of Assertive Outreach and Crisis Resolution services across the UK. 23,24 We found several statistically significant associations at patient and local-area levels. Black pPatients of Black ethnicity were almost three times more likely to be admitted compulsorily than White patients, in keeping with evidence from elsewhere, 25 and after adjusting for areaand Provider Trust-level characteristics.…”
Section: Main Findingsmentioning
confidence: 78%
“…A study of a CRT in Wales 15 found overall bed usage unchanged, attributed to a reduction in informal admissions coinciding with compulsory admissions increasing. Similarly, another study, in England, found no differences, although it lacked statistical power.…”
Section: Voluntary Admission Rates and Durationmentioning
confidence: 99%